(Effect Planting distances and Foliar spray of Chelated Iron on some quantity characters of Corn yield (Zea mays L. - Abdel Karim, Ayman Ahmed; Abdel Rahman, Wael Fahmy; Al - Mahdawi, Nasreen Sbar (Journal of agricultural, environmental and veterinary sciences, 2018)
A field experiment was conducted during spring season 2016 at farm in Bani Saad –Diyala Governorate. (RCBD) was used in experiment in which they were three planting distances (15، 30 and 45)cm and spraying three concentrations of chelated Iron (0، 25 and 50) mg. l-¹.  The results showed that 15 cm distance caused increase in grain yield، Which was 12. 58 t. ha-1.  the 30cm distance treatment superior in most characters such as ear length، number of rows and number of grain per ear، Which were 4. 39 cm، 17. 79 row and 493. 30 grain respectively.  while 45cm distance decreased in some characters.  Using iron concentration at 50 mg Fe. L-¹ caused significant differences in ear length، number of rows per ear، number of grain per ear and grain yield as compared with control , and they were 23. 50 cm، 17. 51 row، 522. 30 grain and 7. 99 t. ha-1 respectively.  The results also showed that the interaction between distances and spraying tratments 30cm * 50 mg Fe.  L-¹ gave significant effect in more plant characters compared with the other interactions treatments.  Although that 30cm distance treatment was superior in most characters but didn’t substitute the number of plants founded in 15cm distance treatment، and this reflected in grain yield per area it.
Keywords: foliar spraying; cultivation distances; chelated iron; Yield; yellow corn